(untitled) (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
The presence and deteriorating action of microorganisms on monuments and stone works of art have received considerable attention in the last few years. Knowledge of the microbial populations living on stone materials is the starting point for successful conservation treatment and control. This review describes some biodegradation processes originating from activity of microorganisms in black microbial crusts growing on historic monuments. The crusts are mainly composed of gypsum, carbonaceous particles and polycyclic aromatic carbons. They are slowly dissolving gypsum from black crusts represent a continuous source of sulphur for microbial growth. The sulphate bonding capacity of the sheath of cyanobacteria causes a particularly high demand for sulphate, thus making sulphur nutrition a relevant aspect in their physiology. Growing concern for the preservation of cultural heritage has led to a greater interest in the biological attack on these monuments. The importance of cyanobacteria as deteriogens is emphasized and the traditional and more modern molecular methods used to detect microorganisms are discussed.